Dual biological role and clinical impact of de novo chromatin activation in chronic lymphocytic leukemia - Chapaprieta, Vicente; Maiques-Diaz, Alba; Nadeu, Ferran; Clot, Guillem; Massoni-Badosa, Ramon; Mozas, Pablo; Mateos-Jaimez, Judith; Vidal, Anna; Charalampopoulou, Stella; Duran-Ferrer, Martí; Royo, Romina; Russiñol, Núria; et al. (Blood, 2025)
Previous studies have reported that chronic lymphocytic leukemia (CLL) shows a de novo chromatin activation pattern compared with normal B cells. Here, we explored whether the level of chromatin activation is related to the clinical behavior of CLL. We identified that, in some regulatory regions, increased de novo chromatin activation is linked to clinical progression, whereas, in other regions, it is associated with an indolent course. We next developed 2 prognostic scores for progressive and indolent disease, respectively, calculated a single score representing the balance between them, and further generated surrogate scores based on gene and protein expression of the target genes. The balance score outperformed the clinical impact of the 2 individual scores, because it seemed to capture the prognostic information provided by each of them. Biologically, CLLs with higher balance score showed increased activation of tumor necrosis factor alpha (TNF-α)/NF-κB and mTOR signaling pathways. Regulatory programs related to progression were predominantly activated in the lymph node microenvironment, whereas those linked to indolent disease appeared to be microenvironment independent. Finally, we thoroughly validated the balance score as a powerful and independent quantitative prognostic factor for time to first treatment across independent CLL cohorts and data modalities, such as chromatin, transcriptome, or proteome data. Our findings support the concept that de novo acquisition of chromatin changes in CLL cells plays a dual biological role, and the balance between proprogression and proindolence is a strong independent determinant of CLL prognosis.
Zuerst veröffentlicht: 22. Januar 2025
Gesehen am 24.09.2025